Implementation of GeoGebra-based LMS canvas on conceptual understanding of geometry transformation of grade XI students - Santosa, Yoga Tegar; Maulida, Dini Wardani; Murtiyasa, Budi (Universitas PGRI Semarang, 2025)
One of the most important things that students must learn in mathematics is conceptual understanding skills. However, in reality, students' conceptual understanding skills is often still low. The aims of this study is to test the difference in conceptual understanding between students who use the Geogebra-based Learning Management System (LMS) Canvas and those who do not use the media. This study uses a quasi-experimental quantitative type with a pretest and posttest non-equivalent control group design. The research subjects consisted of students in grade XI MIPA 1 and MIPA 2 at one of the high schools in Boyolali, each of which amounted to 36 students. The validated mathematical conceptual understanding skill test is applied as a research instrument. Descriptive and inferential statistics are used in data analysis. The results showed that there was a significant difference in student's conceptual understanding skills in the experimental and control classes.Â In addition, the results showed that compared to the control group, the experimental group had superior conceptual understanding skills. This is shown by the median and mean rank of students' posttest scores in experimental class (median = 80; mean rank = 51.25), higher than in control class (median = 46; mean rank = 21.75).